SOSIALISASI DAN EDUKASI PERAN PERAWAT SEBAGAI EDUKATOR DIRUANG HEMODIALISIS RUMAH SAKIT DEWI SRI KARAWANG - Sugihartati, Nining; Asih, Okti Rahayu; Sumitro, Sumitro; Hafid, Indah Fitria; Kharisma, Dinda (LP2M STP Mataram, 2024)
Chronic kidney disease is a significant kidney damage, which can be experienced by all groups, with the biggest problem being hypervolemia. Pharmacological efforts are carried out by providing furosemide therapy which acts as a diuretic, while non-pharmacological efforts are to carry out routine care efforts, dietary management, fluid restriction, increased knowledge and health education. This community service activity aims to provide socialization and education on the importance of the role of nurses as educators to improve the compliance of patients undergoing hemodialysis therapy at Dewi Sri Karawang Hospital. The method used in this community service activity is to provide counseling and education to nurses about the importance of carrying out the role of educator at every stage of patient care in the hemodialysis room not only to patients but also to their families by using module media on how to care for patients undergoing hemodialysis therapy to all nurses in the hemodialysis room. The results of this community service are an increase in hemodialysis therapy compliance in the hemodialysis unit at Dewi Sri Karawang Hospital